RELATIONSHIP BETWEEN ALTITUDINAL CHANGES AND DISTRIBUTI OF RATS : A PRELIMINARY STUDY FROM GUNUNG BOTOL GUNUNG HALIMUN NATIONAL PARK - Maharadatunkamsi Maharadatunkamsi (BERITA BIOLOGI, 2001)
A study on the distribution and abundance of high mountain rat was carried out at Gunung Botol, Gunung Halimun National Park.Observation was conducted at three stations located at the mountain top, middle and foot of the mountain.The results indicated that four species of rat were recorded from Gunung Botol, namely Maxomys bartelsii,Niviventer lepturus, Niviventer fulvescens and Niviventer cremoriventer.Our data showed a relationship between number of individuals observed of each species with altitudinal gradients.While estimation of murid rodent population between altitudinal changes indicated there was no differences between the stations observed. An analysis was conducted to investigate any possible association between rat abundance against environment factors that could associate with altitude.The results indicated that ground covering and tree circumference, as well as interspecific competition seemed to be important factors in influencing the differences in distribution of each rat species.